Shafi's law of shops & establishments : containing West Pakistan Shops & Establishment Ordinance, 1969, West Pakistan Shops & Establishments Rules, 1969 - Shafi, Mohammad, 1900- (Bureau of Labour Publications, 1980)
With commentary.